Knockdown of FGFR3 inhibits the proliferation, migration and invasion of intrahepatic cholangiocarcinoma. Issue 3 (March 2023) - Chen, Yi-hui; Yang, Shao-hua; Liu, Li-xin; Hu, Sheng; Wang, Xue-jun; Liao, Zhou-jun; Huan, Yun-feng; He, Kai; Zhang, Xiao-wen
Abstract: The FGF/FGFR signaling axis deregulation of the fibroblast growth factor receptor (FGFR) family is closely related to tumorigenesis, tumor progression and drug resistance to anticancer therapy. And fibroblast growth factor receptor 3 (FGFR3) is one member of this family. In this study, we aimed to investigate the effect of siRNA-induced knockdown of FGFR3 on the biological behaviors of intrahepatic cholangiocarcinoma (ICC). The expression levels of FGFR3 were determined in three intrahepatic cholangiocarcinoma cell lines RBE, HUCCT1 and HCCC9810 cell lines by Western blot. FGFR3 expression in RBE cell line was knocked down by siRNA. Our study found that knockdown of FGFR3 inhibited the migration, invasion and proliferation of ICC cells using Wound healing assay, Transwell migration and invasion assays and Cell proliferation assay. And significantly down-regulated the protein expression levels of MMP2, cyclinD1, and NCadherin, but had no significant effect on MMP9, cyclinD3, vimentin, E-cadherin protein. In addition, we found that ERK/c-Myc presumably is its signaling pathway by bioinformatics analysis and Western blot verification. To sum up, knockdown of FGFR3 inhibited the migration, invasion and proliferation of ICC cells. It demonstrated that FGFR3 probably becomes a therapeutic target for ICC and increases the proportion of potentially curable intrahepatic cholangiocarcinoma patients treated with FGFR inhibitors.